Pengaruh Green Human Resource Management terhadap Green Behavior Karyawan pada PMKS PT. Buana Sriwijaya Sejahtera - Muhammad Apriyanza; Dina Mellita; Efan Elpanso; Heriyanto; Andrian Noviardy (BADAN PENERBIT STIEPARI PRESS, 2025)
Green Human Resource Management (GHRM) has emerged as a strategic approach to integrate environmental sustainability principles into human resource practices. This study aims to examine the effect of GHRM on employees’ green behavior at PT Buana Sriwijaya Sejahtera. Using a quantitative approach with a survey method, data were collected from employees through structured questionnaires and analyzed using regression analysis. The results indicate that GHRM has a positive and significant influence on employees’ consistent engagement in environmentally friendly behaviors. Key factors such as continuous training, supportive incentive systems, active employee involvement, and the alignment of HR policies with sustainability principles were found to play a crucial role in fostering a green organizational culture. These findings imply that organizations seeking to promote environmental awareness and sustainable practices should strengthen their GHRM implementation. This research is limited to a single company, and future studies are recommended to expand the scope to different industries and company scales, incorporating moderating or mediating variables such as green leadership or organizational commitment.